2017
DOI: 10.1370/afm.2043
|View full text |Cite
|
Sign up to set email alerts
|

Access to Primary Care Appointments Following 2014 Insurance Expansions

Abstract: Contrary to widespread concern, we find no evidence that the millions of individuals newly insured through the ACA decreased new-patient appointment availability across 10 states as shown by stable wait times and appointment rates for private insurance as of mid-2014.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 12 publications
2
9
0
Order By: Relevance
“…Factors contributing to this variability include county-level Medi-Cal population differences, relative shortages of PCCs accepting new Medi-Cal patients, and number of FQHCs, as well as countylevel structural and organizational factors related to Medi-Cal managed care plans. Although prior work from other states has suggested that increased reimbursement to Medicaid clinicians may improve appointment availability, 10,11,21 our finding of variation across counties in the same state confirms that other factors are also important.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Factors contributing to this variability include county-level Medi-Cal population differences, relative shortages of PCCs accepting new Medi-Cal patients, and number of FQHCs, as well as countylevel structural and organizational factors related to Medi-Cal managed care plans. Although prior work from other states has suggested that increased reimbursement to Medicaid clinicians may improve appointment availability, 10,11,21 our finding of variation across counties in the same state confirms that other factors are also important.…”
Section: Discussionsupporting
confidence: 68%
“…A similar study adding FQHCs to the sampled practices in the same 10 states found comparable results. 21 These analyses did not account for variation by state in the number of new enrollees needing an appointment with a PCC. Our simulated experience of locating primary care for individuals and families with Medi-Cal coverage is consistent with the typology of DeVoe et al 5 suggesting that access to care is a critical priority.…”
Section: Discussionmentioning
confidence: 99%
“…In 10 diverse states, by the measure of median wait times for new appointments, there was no evidence of being overwhelmed. 12 …”
Section: High-level Influencesmentioning
confidence: 99%
“…This sentiment was expressed by Centers for Medicare and Medicaid Services (CMS) Administrator Seema Verma, who noted that Medicaid would fail to live up to its promise if it Bmerely provides a card without care.^3 These concerns are not unwarranted; simulated patient studies have concluded that commercially insured patients' ability to secure appointments in primary care settings is about 25 percentage points higher than Medicaid patients', 4,5 with access for Medicaid patients improving slightly following the ACA's 2014 Medicaid expansion. 6,7 Empirical evidence about access to care can help inform debate about the relative value of the Medicaid program. Studies of differences in access to primary care have not been consistent, [8][9][10][11][12] and less is known about variability in access across urban or rural areas, 13,14 particularly when it comes to accessing mental health care (an important service for Medicaid enrollees), or other types of specialty care.…”
Section: Introductionmentioning
confidence: 99%